Marriage of Muslim to Christian or Jews Woman and its Implications Under Islamic Law - Abubakar Ibrahim Adamu; Hamidu Ardo (Penerbit Hellow Pustaka, 2025)
Muslim marriage to Christian and Jews is a controversial topic in Islam. While some Islamic scholars argue that it is permissible others argue that it is forbidden. This paper will discuss the implications of Muslim marriage to Christian and Jews in Islam. It will examine the various opinions of Islamic scholars on the implications of such marriage on Islamic faith. It will also discuss the potential benefits and drawbacks of such marriage and the potential implications for the Islamic community. Finally it will consider the implications of the marriage in Islam.